THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE TRANSLATION PROFESSION: A COMPETENCY-BASED ANALYSIS - Asmar, Hidayatul Fajri; Nappu, Syamsiarna; Daddi, Herlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the impact of artificial intelligence (AI) on the translation profession through a competency-based lens. It investigates how AI has changed the work pattern of translators and identifies both technical and non-technical competencies essential for translators to remain relevant in the AI era. Using a qualitative descriptive method, data were collected through semi-structured interviews with professional translators who are members of the Indonesian Translators Association (HPI) in South Sulawesi. The findings indicate that while AI improves time efficiency and offers translation assistance, it still cannot replace human involvement in cultural and contextual translation aspects. The study highlights key skills required by translators such as CAT tool proficiency, post-editing capabilities, cultural awareness, critical and analytical thinking, decision-making, and endurance. These results provide practical implications for translator education and professional development in the age of automation.